Proses Seleksi Karyawan, Metode dan Teknik Wawancara - Wiguna, Wahyu; Fikri Hawari; Indri Priyono; Lily Chairunnisa; Lufi Wulandari; Amelia Farida (IPM2KPE, 2026)
This study aims to analyze the employee selection process and the interview methods and techniques used to recruit human resources suited to the company's needs. The research method used was a qualitative approach, using interviews with HR Management at a manufacturing company located in Serang, Banten. The results indicate that the selection process involves several stages: CV screening, psychological testing, user interviews, HR Manager interviews, General Manager interviews, and Director interviews. The interview process is differentiated based on job categories: operator and staff. At the operator level, interviews emphasize work attitude, motivation, and interpersonal skills, while at the staff level, a structured, competency-based approach, such as the STAR (Situation, Task, Action, Result) method and the Behavioral Event Interview (BEI), is used to explore candidates' analytical, conceptual, and leadership abilities. The study concludes that a systematic, structured, and competency-based selection and interview process can help companies recruit candidates who meet job requirements and have the potential to become future talent or leaders. Keywords: Employee Selection, Job Interview, Human Resource Management